The Lexical Ambiguity in News Headlines of the Jakarta Post - Saputri, Ni Komang Desey Trisna Dewi; Suastra, I Made; Sumaryana Putra, I Komang (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p04, 2022)
The title of this study is “ Lexical Ambiguity in News Headlines of The Jakarta Post” . This study deals with lexical ambiguity and its factors . This study aims to identify the lexical ambiguity and analyze the factors of lexical ambiguity . The data was taken from The Jakarta Post’s articles that were published throughout 2019-2021 . The documentation method and the note-taking technique were used in collecting the data. The data was analyzed by using the theory of lexical ambiguity proposed by Ullmann (1967) . The result s of the study show ed that there are four words found as lexical ambiguity and two factors of lexical ambiguity, namely polysemy and homonymy. The words ‘flood’ and ‘ghosting’ are classified as homonymy, and the words ‘promise’ and ‘curfew’ are classified as polysemy.